2017
DOI: 10.1016/j.jsat.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Contingent Vs. Non-Contingent Rewards: Time-Based Intervention Response Patterns Among Stimulant-Using Men Who Have Sex With Men

Abstract: Stimulant use rates are higher among men who have sex with men (MSM) than the general population. Contingency management (CM) may be an effective intervention for reducing stimulant use in this population. To specify both the mechanism and temporal effects of contingent reward on behavior change, logistic growth trajectory modeling (LGTM) was used to contrast a non-contingent matched rewards condition (i.e., non-contingent yoked controls; NCYC) to a voucher-based CM intervention (maximum= $430) to reduce stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Our findings highlight the syndemic nature of these minority stress conditions and suggest the need to approach to prevention and treatment at multiple levels. Substance abuse intervention research has found contingency management (CM) to be efficacious in reducing methamphetamine use in MSM, especially those who are homeless or resource-deprived, as such incentives can also benefit basic survival needs such as food and shelter (Bourne and Weatherburn, 2017; Carrico et al, 2016; Reback et al, 2010; Shoptaw et al, 2017). In light of the current findings, CM approaches that incorporate psychosocial sessions that help MoCSM copy with homophobic victimization, provide linkages to community and economic resources tailored for MoCSM can have greater impact on reducing these adverse syndemic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings highlight the syndemic nature of these minority stress conditions and suggest the need to approach to prevention and treatment at multiple levels. Substance abuse intervention research has found contingency management (CM) to be efficacious in reducing methamphetamine use in MSM, especially those who are homeless or resource-deprived, as such incentives can also benefit basic survival needs such as food and shelter (Bourne and Weatherburn, 2017; Carrico et al, 2016; Reback et al, 2010; Shoptaw et al, 2017). In light of the current findings, CM approaches that incorporate psychosocial sessions that help MoCSM copy with homophobic victimization, provide linkages to community and economic resources tailored for MoCSM can have greater impact on reducing these adverse syndemic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Out of 28 methamphetamine use interventions, 13 focused on reducing use among current users or among those at risk for use (Carrico et al, 2018;Carrico, Gómez, et al, 2015;Landovitz, Fletcher, Shoptaw, & Reback, 2015;Reback, Fletcher, Shoptaw, & Mansergh, 2015;Reback, Fletcher, Swendeman, & Metzner, 2019;Reback et al, 2012;Reback & Shoptaw, 2014;Shoptaw, Landovitz, & Reback, 2017;Shoptaw et al, 2008;Wu et al, 2011;Zhang, Shoptaw, Reback, Yadav, & Nyamathi, 2018;Zule et al, 2012); 10 interventions focused on individuals who met criteria for methamphetamine use disorder (Coffin et al, 2018;Colfax et al, 2011;Das et al, 2010;Landovitz et al, 2012;Lea et al, 2017;McElhiney et al, 2009;Mimiaga, Pantalone, et al, 2019;Reback et al, 2010;Reback, Rünger, Fletcher, & Swendeman, 2018;Shoptaw et al, 2005). The other five studies evaluated interventions for individuals who used methamphetamine, regardless of whether they met criteria for methamphetamine use disorder (Burgess et al, 2018;A.…”
Section: Methamphetaminementioning
confidence: 99%
“…Psychosocial interventions are first line treatment for stimulant use disorders, with pharmacological interventions being largely ineffective ( Chan et al, 2019 ; De Crescenzo et al, 2018 ). There is strong evidence that CM is an effective intervention for stimulant use disorders ( Carrico et al, 2018 ; De Crescenzo et al, 2018 ; Higgins, Wong, Badger, Ogden, & Dantona, 2000 ; McDonell et al, 2013 ; McPherson et al, 2018 ; Petry, Alessi, Olmstead, Rash, & Zajac, 2017 ; Rawson et al, 2006 ; Shoptaw et al, 2005 ; Shoptaw, Landovitz, & Reback, 2017 ; Vocci & Montoya, 2009 ).…”
Section: Effectiveness Of Contingency Management (Cm)mentioning
confidence: 99%
“…Given the broad applicability of CM, including promoting healthy behaviors ( Landovitz, Fletcher, Shoptaw, & Reback, 2015 ; McPherson et al, 2018 ; Rash, Stitzer, & Weinstock, 2017 ; Shoptaw et al, 2017 ), we suggest expanding its use during the COVID-19 pandemic.…”
Section: Expanding the Use Of CM During The Covid-19 Pandemicmentioning
confidence: 99%